Molecular studies of bioactive peptides of Nile tilapia (Oreochromis niloticus) skin protein hydrolysate DLBS3D33 as MMP-2 inhibitor - Sherlyn P. Wijaya, Puji Rahayu, Maggy T. Suhartono,, Raymond Tjandrawinata, (Journal of Applied Pharmaceutical Science, 2023)
Proteins of the Nile tilapia skin have long been known to possess wound-healing activity even though the mechanism underlying this effect is still unclear. There are indications that the timely decrease of matrix metalloproteinase-2 (MMP-2) concentration after the inflammation-triggered increase is one of the important factors affecting the progression of wound healing. Thus, in this study, the MMP-2 inhibitory ability of Nile tilapia skin protein hydrolysate DLBS3D33 was assessed with in vitro reverse gelatin zymography. The molecular weight distribution and secondary structure of DLBS3D33 were characterized with size exclusion chromatography and Fourier transform infrared spectroscopy whereas each peptide species was isolated with thin-layer chromatography. The result suggested that DLBS3D33 had six different peptides, with ~60% of the peptides sized below 600 Da and in an α-helix or coiled structure. These peptides showed an MMP-2 inhibitory effect, with 50% inhibition of 1 μg MMP-2 achieved with 35.3–41.2 mg of the DLBS3D33 protein. Hence, the hydrolysis of Nile tilapia skin successfully produced bioactive peptides with MMP-2 inhibitory activity.
Keywords: Bioactive peptides, Nile tilapia, Oreochromis niloticus, MMP-2 inhibitor, protein characteriz